The Theatre of Senses: New Perspectives of Research (Itinera, 2017)
In the articulation of Western thought, the senses of taste, smell and touch have been marked by exclusion, if not by condemnation and repression, compared to the more “noble” senses of sight and hearing. The European project “Senses” was born precisely on the basis of this question that concerns the opposition and the hierarchy of the senses. It investigates the ways in which theatre addresses and uses the senses of the spectator, and the possibility that theatre may stimulate a larger and more complex sensoriality. For this reason, the project also deals with the importance of Aesthetics, as a philosophical discipline which aims at understanding how the senses work and at shedding new light on the meaning of the performative aspect that characterizes the contemporary scenic arts.